2013
DOI: 10.1103/physrevb.87.144507
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of the triplet spin-valve effect in a superconductor-ferromagnet heterostructure

Abstract: The theory of superconductor-ferromagnet (S-F) heterostructures with two ferromagnetic layers predicts the generation of a long-range, odd-in-frequency triplet pairing at non-collinear alignment (NCA) of the magnetizations of the F-layers. This triplet pairing has been detected in a Nb/Cu 41 Ni 59 /nc-Nb/Co/CoO x spin-valve type proximity effect heterostructure, in which a very thin Nb film between the F-layers serves as a normal conducting (nc) spacer. The resistance of the sample as a function of an external… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
87
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 41 publications
5
87
0
4
Order By: Relevance
“…Those groups found evidence for spin-triplet generation occurring during the magnetization reversal process while sweeping an external magnetic field. Better control of the magnetic states has been achieved recently by several groups measuring the critical temperature T c of S/F/F trilayers, where generation of spin-triplet correlations results in lowering of T c [21][22][23][24][25][26]. Controlling T c , however, is less likely to be useful for future device applications than controlling supercurrent.…”
mentioning
confidence: 99%
“…Those groups found evidence for spin-triplet generation occurring during the magnetization reversal process while sweeping an external magnetic field. Better control of the magnetic states has been achieved recently by several groups measuring the critical temperature T c of S/F/F trilayers, where generation of spin-triplet correlations results in lowering of T c [21][22][23][24][25][26]. Controlling T c , however, is less likely to be useful for future device applications than controlling supercurrent.…”
mentioning
confidence: 99%
“…As with the conventional superconductor-normal metal proximity effect, the increased 'leakage' of pairs from the S layer should reduce the singlet pair amplitude within it and hence decrease the T C of the structure 12 . A number of experiments have been performed to test these predictions: for example, in S-F 0 -F structures, both Leksin et al 13 and Zdravkov et al 14 recently demonstrated a minimum in T C when the F and F 0 layers were orthogonal-the configuration that theoretically maximizes singlet-triplet pair conversion.…”
mentioning
confidence: 99%
“…The observed angular dependence of the superconducting transition temperature T c is caused by a combination of the singlet and triplet components of the superconducting condensate. The existence of the triplet contribution to the superconducting spin-valve effect has also been shown in [11][12][13][14][15]. An important question for basic and applied research in the field of spintronics is whether there is the possibility of observing the "isolated" triplet contribution to the superconducting spin-valve effect.…”
Section: Introductionmentioning
confidence: 97%